PENGARUH PENILAIAN PRESTASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (STUDI PERAWAT RSIA ERIA BUNDA PEKANBARU) - Ainaya Alfatihah; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the effect of work performance appraisal and work discipline on nurse performance partially and simultaneously. This study used a questionnaire as a means of collecting data which was distributed to 55 respondents to the nurses RSIA Eria Bunda Pekanbaru. The data is then processed using descriptice analysis an statistical analysis using SPSS by conducting validity, reability testing, simple linear regression analysis, multiple linear analysis, determination analysis (), and hypothesis testing with t test (partial test) and F test (simultaneous).         The results of the research show that testing the first hypothesis is the assessment of work performance on the performance of nurses, namely  (3,920) >   (1,674) it means that work performance appraisal has a significant effect on nurse perfomanc. The second Hasil uji   (12.550) >  (3,18), it means that work discipline has a significant effect on the performance of nurse. Keywords : Work Performance Appraisal, Work Discipline, Nurses   performance